Empowering the police during COVID-19: How do normative and instrumental factors impact public willingness to support expanded police powers? - Sargeant, Elise (Criminology & criminal justice, 2024)
This article seeks to test the police ‘empowerment hypothesis’ to better understand public support for police powers during the COVID-19 pandemic. To do so, we draw on Australian survey data to compare the efficacy of the instrumental and normative models of police empowerment to enforce social distancing regulations. We find that instrumental concerns about risk dominate participants’ willingness to empower the police during the COVID-19 pandemic. However, when it comes to what police can do to encourage police empowerment, procedural justice appears to be more important than police effectiveness, supporting the normative model. Our article adds to the limited but growing body of research that examines the correlates of police empowerment and the conditions under which members of the public are willing to grant police expanded powers.